Participation of local people in water management: evidence from the Mae Sa Watershed, northern Thailand - Heyd, Helene; Neef, Andreas (International Food Policy Research Institute, 2004)
In the early 1990s, Thailand launched an ambitious program of decentralized governance, conferring greater responsibilities upon sub-district administrations and providing fiscal opportunities for local development planning. This process was reinforced by Thailand’s new Constitution of 1997, which explicitly assures individuals, communities and local authorities the right to participate in the management of natural resources.